2022
DOI: 10.35445/alishlah.v14i2.1824
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Motivation in English Learning amid Covid-19 Pandemic: A Systemic Functional Linguistics Perspective

Abstract: The pandemic of covid-19 has had a negative impact on schooling quality around the world. The lack of student enthusiasm to learn using digital platforms is one issue leading to the low quality of education. Several prior types of research have looked into how students perceive their motivation to learn in the face of pandemic covid-19. However, modal analysis to reveal students' motivation through their written personal views on learning during the epidemic of Covid-19 remains a relatively unexplored area. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Various studies revealed that the use of podcasts not only improves listening skills but also effectively motivates students in their English language learning activities (Abdulrahman et al, 2018;Rahman et al, 2018;Indahsari, 2020). These studies highlights the significant influence of integrating podcasts in education and it proved to be a valuable tool for students, enriching their language skills and empowering them to recognize their own strengths while building the necessary confidence to master the language (Deswarni, 2016).…”
Section: The Effect Of Using Voa Podcast On Students Intensive Listen...mentioning
confidence: 93%
See 1 more Smart Citation
“…Various studies revealed that the use of podcasts not only improves listening skills but also effectively motivates students in their English language learning activities (Abdulrahman et al, 2018;Rahman et al, 2018;Indahsari, 2020). These studies highlights the significant influence of integrating podcasts in education and it proved to be a valuable tool for students, enriching their language skills and empowering them to recognize their own strengths while building the necessary confidence to master the language (Deswarni, 2016).…”
Section: The Effect Of Using Voa Podcast On Students Intensive Listen...mentioning
confidence: 93%
“…Rost (2015) further emphasizes the four factors that contribute to the struggles of EFL students in learning listening: neurological development, motivational issues, input, and transfer techniques. Additionally, Deswarni (2016) emphasizes the importance of motivation in English language learning, as it empowers students to recognize their strengths and build the confidence needed for language mastery. These factors significantly influence EFL students' ability to comprehend spoken English effectively, highlighting the need for targeted interventions and instructional strategies to address these challenges.…”
Section: The Effect Of Using Voa Podcast On Students Intensive Listen...mentioning
confidence: 99%